Implementation of Industrial Work Practice Model to Improve Student Competence at State Vocational School 1 Tombariri - Lordy Frangky Karel; Efraim R. S. Moningkey; Glenn D.P Maramis; Parabelem Tinno Dolf Rompas (International Journal of Information Technology and Education, 2026)
This study aims to evaluate the implementation of industrial work practice (prakerin) in terms of: 1) context, which includes the objectives of the prakerin program, cooperation between DU/DI and schools based on the MoU, and the expectation that the implementation of prakerin is in accordance with the implementative curriculum; 2) input, which includes the readiness of participants, schools, and DU/DI in implementing prakerin, the absorption of provision materials from schools and DU/DI, and the realization of the implementation of the implementative curriculum; 3) process, which includes student monitoring and guidance, student involvement/participation, student cooperation and problem-solving skills; 4) product, which includes the improvement and mastery of competencies and certification of students after the implementation of prakerin. This study is an evaluation study with a quantitative descriptive approach. The evaluation model used is the CIPP (Context, Input, Process, Product) model evaluation developed by Stufflebeam. Respondents in this study consisted of a vice principal for public relations/head of the industrial work experience working group, 18 supervising teachers, 18 industrial supervisors from Minahasa Regency, Tomohon City, Manado City and 110 students participating in the industrial work experience in 2025. Data were collected through questionnaires, observations, interviews and documentation and analyzed descriptively. The results of the study showed that: (1) the context of implementing industrial work experience at SMK Negeri 1 Tombariri was appropriate, with an achievement percentage of 72.67% for student respondents, 48.06% for supervising teachers, and 46.17% for industrial work experience supervisors, however, in planning, compiling, and synchronizing competencies, it is necessary to involve industrial work experience elements, and the development of industrial work experience cooperation through an MoU has not been realized properly; (2) The input for the implementation of the internship has been appropriate, with an achievement percentage of 64.71% for student respondents, 47.89% for supervising teachers, and 45.39% for DU/DI mentors, but still requires participant readiness in terms of competency where the obstacles faced by students are more related to competency mastery and insufficient work readiness, therefore maximizing the time and material for provision is very necessary; (3) The process of implementing the internship has been appropriate, with an achievement percentage of 84.3% for student respondents, 74.39% for supervising teachers, and 72.22% for DU/DI mentors, but the less than optimal role and responsibility of the mentors causes communication regarding the development of student competencies to be less monitored; (4) The product of the implementation of the internship has been appropriate with an achievement percentage of 47.17% for student respondents, 31.17% for supervising teachers, and 28.72% for DU/DI mentors, this is shown by the changes that have occurred in students in terms of attitude, responsibility and increased competency.